MEDIATYZACJA SPORTU. ZMIANY W MEDIALNYM PRZEKAZIE IGRZYSK OLIMPIJSKICH - Świerczyński, Marek Jarosław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The Olympic Games is a great sporting event as well as the media event. Thanks to the media, millions of fans around the world can participate in the Olympic Games. However, the presence of the media has some consequences and changes the Olympic environment. The transformation, named mediatization, also visible on the Polish media market has been going on ever since radio and television began transmitting Olympic events. However, in the last quarter of a century, through the development of new technologies, changes are much faster. Chronologically, economic, social and private mediatization can be distinguished. Each type caused significant interference in the sporting and organizational spheres of the Olympic Games.